1998
DOI: 10.1073/pnas.95.25.14915
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to the biological effects of polyaromatic hydrocarbons is influenced by genes of the major histocompatibility complex

Abstract: Polyaromatic hydrocarbons are ubiquitous environmental chemicals that are important mutagens and carcinogens. The purpose of this study was to determine whether genes within the major histocompatibility complex (MHC) inf luence their biological activities. Cell-mediated immunity to dimethylbenz(a)anthracene (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
3
25
0
2
Order By: Relevance
“…In addition to activation by LPS signaling, TLR4 is also associated with signaling by many environmental chemicals, many of which are tumorigenic (23). Stimulation of TLRs by various ligands leads to signaling pathways that activate not only innate but also adaptive immunity by antigen-presenting cell (APC)-dependent or APC-independent mechanisms (5).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activation by LPS signaling, TLR4 is also associated with signaling by many environmental chemicals, many of which are tumorigenic (23). Stimulation of TLRs by various ligands leads to signaling pathways that activate not only innate but also adaptive immunity by antigen-presenting cell (APC)-dependent or APC-independent mechanisms (5).…”
Section: Discussionmentioning
confidence: 99%
“…The development of that response is controlled by genes at the MHC class I and Ah receptor loci (15). Moreover, allergic contact hypersensitivity was associated with inhibition of tumor development, giving rise to the hypothesis that induction of the T cell-mediated immune response to DMBA protects an individual from the carcinogenic effects of that agent.…”
Section: Introductionmentioning
confidence: 99%
“…Strains of mice that were homozygous for the d allele (strains that are inefficient at metabolizing PAHs) uniformly failed to develop DMBA contact hypersensitivity (Anderson et al, 1995). Some strains that were homozygous for the b allele developed contact hypersensitivity to DMBA, but this was not universally the case, suggesting that other genetic factors were involved in the control of contact hypersensitivity to DMBA (Elmets et al, 1998). To further investigate the genetic component responsible for induction of cutaneous cell-mediated immune responses to PAH, strains of congenic mice that differed only at the major histocompatibility complex (MHC) were tested for their ability to develop this type of reaction.…”
Section: Strain Variation To the Development Of Cell-mediated Immunitmentioning
confidence: 99%
“…To further investigate the genetic component responsible for induction of cutaneous cell-mediated immune responses to PAH, strains of congenic mice that differed only at the major histocompatibility complex (MHC) were tested for their ability to develop this type of reaction. Those studies indicated that, in addition to the Ah receptor locus, proteins encoded by genes within the major histocompatibility locus also participated in the induction of this type of immune response (Elmets et al, 1998). Mice that possessed the H-2 k and closely related H-2 a loci had significantly greater contact hypersensitivity responses than mice with non-H-2 k or non-H-2 a loci.…”
Section: Strain Variation To the Development Of Cell-mediated Immunitmentioning
confidence: 99%
See 1 more Smart Citation